Succeeding at business in Southeast Asia : common mistakes companies make - Moraczewski, Eric (Wiley, 2020)
"The United States makes up five percent of the world economy (based upon population). This is a large number for one country, but it also shows that there's immense potential outside of the US market. Today, Asia makes up roughly 60 percent of the world economy based upon population. The Southeast Asian markets have seen immense growth over the last 20 years and continue to evolve every day; perhaps most compelling is the speed at which this demographic is increasing. The time has never been better to do business in Southeast Asia and this bookwill guide readers through the steps necessary to build and execute their market entry strategy"--